The Effect Of Peppermint Aromatherape On Decreasing The Dismenore Discharge Scale In SMPN 4 Satu Atap Geger - Merlyna Suryaningsih; Qurrotu Aini (NHM PRESS, 2020)
Disminorrhea is a menstrual pain that is encountered without abnormalities in genuine genitalia. Based on preliminary study on 10 female students in SMPN 4 Satu Atap Geger there were mild pain 2 people (20%), moderate pain as many as 7 people (70%) and pain 1 person weight (10%). The purpose of this study was to determine the effect of peppermint aromatherapy on decreasing the scale of disminorea pain in female students at SMPN 4 Satu Atap Geger. This research method was Quasy experiment with pretest-posttest approach with control group. The independent variable was peppermint aromatherapy, whereas the dependent variable is the decrease in the pain scale of disminorrhea. The number of population 50 who experienced disminorea, research sample 18 respondents. Then sampling usied purposive sampling technique. Instrument used numerical scale, and analyzed using paired t-test with a: 0,05. The results showed that the pre and post treatment groups analyzed using paired t-test obtained ρ: 0.001 <α: 0.05. This showed that H0 was rejected that there was difference of pain scale of pre and post treatment group. While in the control group that was analyzed using paired t-test test obtained ρ: 0,030 <α: 0,05. This showed that H0 was rejected there was a difference of pain between pre and post control group. In the control group analysis and treatment using independent t-test obtained ρ: 0,000 <α: 0,05. It meant that H0 was rejected, then there is a difference of pain scale level between treatment and control group. Based on the research, peppermint aromatherapy can be used as one of the nonfarmakologi safe to overcome the pain of disminorea.